Owners’/Managers’ Perception on Privatization - Chitrakar, Tara Devi (PYC Nepal Journal of Management, 2011)
The present study was conducted to examine the perception of owners on privatization including its necessity and unnecessary, its impact, process and modalities to be adopted, existing policy, role of government etc. A questionnaire survey of 40 owners found that they were in favor of privatization. They want some measures to be followed before privatization. They viewed its benefits are not reached to the targeted people of the society. They suggested policy improvement and mixed modality to be followed.